Influência da cognição e do metabolismo lipídico-inflamatório-oxidativo no desempenho auditivo de idosos após adaptação de próteses auditivas - Lessa, Alexandre Hundertmarck (2015)
This thesis aimed to track some genetic mutations associated with hearing loss; to assess cognitive status, oxidative stress level, lipid and inflammatory profile also speech perception and auditory processing skills in elderly patients with hearing loss in order to verify the association between these variables and possible influence of these aspects in changing auditory performance after three months of hearing aids use, considering the acclimatization period. For this, 12 hearing-impaired older people were evaluated. Initially, several blood tests to track some genetic mutations and to check their lipid, inflammatory and oxidative metabolism were done. Cognitively, they were evaluated by the Consortium to Establish a Registry for Alzheimer's Disease; as the hearing abilities of temporal resolution and ordering, and binaural separation and integration through the Random Gap Detection Test, Duration and Pitch Pattern Sequence tests, Dichotic Digits Test; regarding speech perception the patients were evaluated by obtaining Sentences Recognition Indexes in Silence and Noise through the Lists of Sentences in Brazilian Portuguese. After all these evaluations, geriatric patients made use of hearing aids for three months and had auditory skills and measures related to speech perception assessed again. The data were correlated statistically. None of the subjects presented any tested genetic mutations. By analyzing only the initial data, the auditory abilities of temporal ordering and resolution were correlated with some cognitive assessments and oxidative stress levels; concerning the speech recognition, measures were correlated only with some oxidative stress levels. With regard to the difference in performance between pre-hearing aid fitting evaluation and after the acclimatization period, the hearing abilities of temporal ordering and resolution, and binaural integration, had an inverse correlation with some cognitive assessments; it was also observed that the improvement in temporal resolution ability was correlated with high levels of an inflammatory cytokine and low levels of a oxidative stress marker; otherwise the comparison of results between speech perception evaluations, none of the variables showed a statistically significant difference. Thus, it was realized that even cognitive impaired older people present possibility of stimulating neural plasticity; moreover it also found that auditory skills, especially those related to the temporal auditory processing, and the speech perception in quiet and noisy situations, suffered some influence, especially by oxidative stress levels, measured through blood tests.